Hydatid Cyst in the Pulmonary Artery: A Systematic Review - Dlsoz M. Hussein; Fahmi H. Kakamad; Bnar J. Hama Amin; Dana H. Baqi; Soran H. Tahir; Abdulwahid M. Salih; Razhan K. Ali; Fattah H. Fattah; Gasha S. Ahmed; Berun A. Abdalla; Hussein M. Hamasalih; Hiwa O. Abdullah; et al. (Barw Medical Journal, 2023)
AbstractIntroductionIt is uncommon to have a hydatid cyst in the pulmonary artery. Typically, it results from an intracardiac cyst or a surgical cyst rupturing from a hepatic origin. The objective of this systematic review is to describe this rare disease.MethodsThe electronic search engine and database "Google Scholar" and "PubMed" were systematically searched for pertinent publications in the English language.ResultsA total of 45 papers were initially found by the systematic search; however, only 16 studies that comprised 16 patients were included. Eight (50%) of the patients were male and eight (50%) were female. Hemoptysis, dyspnea, bloody sputum, vomiting, and shortness of breath were the clinically significant symptoms. Twelve (75%) of the patients had a history of hepatic hydatid disease, followed by three patients (18.8%) with primary lung cystic lesions, and one (6.3%) patient with primary cardiac lesions. Severe pulmonary hypertension, septic shock, and massive hemoptysis all contributed to the death of three (18.8%) patients.ConclusionLocalization of hydatid cysts inside the pulmonary artery is incredibly uncommon but life-threatening condition. Surgery may be the last remaining choice for some patients.